Analisis Kebutuhan Media E-Karikatur Untuk Menunjang Peningkatan Minat Belajar Sejarah Siswa Pada Pembelajaran Sejarah Kelas X di SMKN 5 Kerinci - Mentari, Yola; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
The background of this research is based on the low interest of students in learning history caused by the use of monotonous and less innovative learning media. This study aims to develop visual learning media in the form of E-caricatures to support increasing interest in learning history of students in the history subject of class X at SMK Negeri 5 Kerinci. The data analysis technique used in this study is descriptive quantitative and qualitative (Mix Method). The technique of collecting data by conducting observations and interviews via google form to 20 students and 1 history subject teacher with direct interviews. The results obtained from observations and interviews are the lack of interest in learning history of students in studying history is caused by non-innovative learning media. Student interest is seen from the dominance of interest indicators such as emotional involvement (30%) and identity connections (40%), while aspects of interest that reflect active involvement and deep understanding such as cognitive involvement (15%), behavioral involvement (10%), and perceptions of historical relevance (5%). Most of the media needs survey, students actually showed interest in visual media, especially images (65%), 13 out of 20 students. Therefore, innovative image-based learning media is needed that is expected to potentially increase students' interest in learning history at SMK Negeri 5 Kerinci. Based on these findings, researchers developed e-caricature visual media to support increasing students' interest in learning history in class X history material at SMK Negeri 5 Kerinci.